Patočka’s Socrates: The Care for the Soul and Human Existence - Učník, L’ubica (Investigaciones Fenomenológicas, 2021)
In order to get out of present day discussions between (for example) determinism and free will, creationism and evolution, bios and zoē, human existence and biological life – those dead end binaries of our present day thinking into which we have manoeuvred ourselves – we need to revisit the Ancient discussions relating to the care of the soul and human existence. I will draw together these two themes from Jan Patočka’s writings by anchor-ing them in his account of Socrates who was the first to emphasise the idea of human re-sponsibility not only for thinking but also for human acting in the world. I will argue that the significant common feature – the care for our own being, our existence – brings Patočka’s reflections on the care for the soul and care for our human existence together. While, according to Patočka, the notion of the care for the soul was displaced from the philosophical reflection by the modern scientific venture, the idea of human existence is, although problematic from the scientific point of view, still a part of our experience. Para librarnos de discusiones contemporáneas entre (por ejemplo) determinismo y libre albedrío, creacionismo y evolución, bios y zoē, existencia humana y vida biológica, estos binomios, callejones de salida del pensamiento de hoy en los que nos hemos metido, tenemos que volver a escuchar las discusiones de la Antigüedad sobre el cuidado del alma y la existencia humana. Voy a recuperar estos dos temas de escritos de Jan Patočka, anclándolos en su interpretación de Sócrates, el primero en poner énfasis en la idea de responsabilidad humana no solo de su pensamiento sino también de su actuar en el mundo. Argumentaré que el significativo rasgo común, esto es, el cuidado por nuestro propio ser, nuestra existencia, es lo que une las reflexiones de Patočka sobre el cuidado del alma y el cuidado de la exitencia humana. Mientras que, según Patočka, la noción del cuidado del alma ha sido desplazada de la reflexión filosófica por la empresa científica moderna, la idea de la existencia humana, a pesar de lo problemático que puede resultar desde un punto de vista científi-co, todavía forma parte de nuestra experiencia.